(untitled) (Revista de História da UEG (REVHIST), 2025)
This article analyzes the competing power projects developed by the factions of the dominant class in Ilhéus during the 1930s, centered on the flow of cocoa through the fluvio-maritime port of Ilhéus, better known as the Port of Pontal. The administration of Eusínio Gaston Lavigne, as mayor of the municipality leading the production of the region’s main export commodity, serves as the lens through which these internal class divisions were exposed and perceived as a threat to the maintenance of the order required for capital reproduction. Lavigne identified the port as a strategic element capable of balancing these conflicts, while simultaneously consolidating his political position and constructing a symbol of regional autonomy on the Atlantic coast. In this context, Bonapartism emerged during the Lavignist administration as a political solution capable of reconciling the interests of the fragmented cocoa-producing dominant class, which needed to be saved from its own internal antagonisms. The sources used include newspaper archives and works produced by Lavigne himself, who left numerous records of his projects for the cacao-growing region. Keywords: Ilhéus. Port of Pontal. Eusínio Gaston Lavigne. Bonapartism.